2012
DOI: 10.1111/ane.12014
|View full text |Cite
|
Sign up to set email alerts
|

The impact of epilepsy on patients' lives

Abstract: The impact of epilepsy is multifaceted and extensive on its effects. The occurrence of seizures is unpredictable and often dangerous, increasing the risk of injury, hospitalization and mortality, and adversely affecting a patient's mental health, often resulting in anxiety, depression or cognitive impairment. Seizures can also result in stigmatization and social exclusion, with detrimental effects on an individual's confidence and self-esteem. However, the burden of epilepsy extends beyond the effects of seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 87 publications
3
71
0
1
Order By: Relevance
“…This study revealed that more than half of the study population (53%) was within the range of 10-30 years of age which is corresponded with Ahmad et al who reported that majority of the patients were within the range of 18-30 years of age [9]. Jenkis (2008) found that incidence of epilepsy was highest among youth patients [11]. …”
Section: Discussionsupporting
confidence: 72%
“…This study revealed that more than half of the study population (53%) was within the range of 10-30 years of age which is corresponded with Ahmad et al who reported that majority of the patients were within the range of 18-30 years of age [9]. Jenkis (2008) found that incidence of epilepsy was highest among youth patients [11]. …”
Section: Discussionsupporting
confidence: 72%
“…This disease can result in life-long disabilities and serious adverse effects on the physical, mental, and socioeconomic status of patients and society (Kerr, 2012). The prevalence of epilepsy is 0.6% of the population, resulting in an estimated $9.6 billion in medical expenses in the United States alone (Yoon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms had significant negative impacts on quality of life in PWE (3). A study on refractory epilepsy demonstrated that depression was a powerful predictor of quality of life, but not seizure frequency (4).…”
Section: Introductionmentioning
confidence: 99%